Microextração líquido-líquido dispersiva em fase reversa para determinação Fe e Cu em óleo vegetal isolante - Tasistro, Ian Bochard (2022)
The substitution of mineral bases produced from petroleum by vegetable bases in lubricating and insulating oils, it is a great opportunity to reduce the emission of pollutants into the atmosphere. In addition, because vegetable oils are biodegradable, they have a lower environmental impact. Vegetable oils are mainly composed of triglycerides (or triacylglycerols), which are esters of fatty acids with glycerol and have several qualities for their use as lubricants and insulators, such as: low volatility, little change in viscosity with temperature changes, and greater solubility for additives than mineral bases. The presence of metals such as Fe and Cu even at low concentrations (mg kg-1) in insulating oils can reduce the breakdown voltage and accelerate the oxidation of insulating oils, so methods with low limits of quantification are required. In the present work, the reverse phase dispersive liquid-liquid microextraction (RP-DLLME) method was used as a sample preparation for extraction and preconcentration of Fe and Cu in vegetable insulating oil, as a green alternative to the methodology proposed by ASTM D7151-15. For the determination of the analytes, flame atomic absorption spectrometry (F AAS) with external calibration was employed. For the method optimization some parameters were evaluated, such as: sample mass, extracting solvent type, dispersing solvent type, extracting solvent concentration, dispersing:extracting solvent ratio, temperature and centrifugation time. For the experiments, assays were performed in triplicate for pure oil samples and oil with the addition of 1 μg g-1 of Fe and Cu, using a standard solution in organic medium. The limits of quantification (LOD) obtained were 0.019 μg g-1 for Cu and 0.035 μg g-1 for Fe, with recoveries of 105% for Cu and 100% for Fe. The results obtained with the proposed method (RP- DLLME and F AAS) were compared with the results obtained by F AAS after the extraction induced by emulsion breakage (EIQE) and there was no statistical difference (Tukey-Kramer test 95% confidence) between the results. The proposed methodology was applied to 5 samples of the insulating vegetable oil in 5 states of use. Finally, a study of the concordance of the proposed method with the 12 principles of green chemistry was performed using the AGREE software. The RP-DLLME stood out for its low cost, simplicity, high analytical frequency and low limits of quantification, besides fitting in with the principles of Green Chemistry with low reagent consumption, less waste generation and with the possibility of using 200 μL of diluted acid as extracting solvent.